How Do They Deal With Speaking Anxiety?: EFL Learners’ Strategies - Idrus, Misnariah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2023)
Emotion promotes various consequences on language learning (Maquidato, 2021). It includes language anxiety. (Brown 2000) defined language anxiety as the